1987
DOI: 10.1021/ed064p291
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry in the dyeing of eggs

Abstract: The coloring of eggs with synthetic dyes is a common tradition associated with the Easter holiday and is an activity well-suited for a variety of simple experiments and demonstrations. We wish to discuss the dyeing of eggs and report some experiments that can be used to study factors influencing the intensity of dye that adheres to the surface of an eggshell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Experiments have been described using eggs in topics ranging from chemical kinetics to biological chemistry. In addition, the distinctive and readily measured optical spectra of porphyrins and their facile synthesis of tetraarylporphyrins have made them popular study objects. The added appeal of using brown eggshells as a naturally occurring porphyrin source lies in the simplicity of the extraction, the low cost, and their availability…”
mentioning
confidence: 99%
“…Experiments have been described using eggs in topics ranging from chemical kinetics to biological chemistry. In addition, the distinctive and readily measured optical spectra of porphyrins and their facile synthesis of tetraarylporphyrins have made them popular study objects. The added appeal of using brown eggshells as a naturally occurring porphyrin source lies in the simplicity of the extraction, the low cost, and their availability…”
mentioning
confidence: 99%
“…As illustrated in Figure S1, kinetic studies revealed a cascade of synthesis mechanisms: (i) porosity-driven chemisorption of Au + ions by the eggshell support as revealed by gradual depletion in the absorbance of ionic Au at 310 nm (Figure S1g) as confirmed by the disappearance of yellow color (Video S1), increased pH (from 2.7 to 6.5), and decreased ionic conductance of the reaction suspension overtime (Figure S1h); (ii) firm binding of Au + ions to negatively charged metal binding surface proteins with open flexible structures and strong electrostatic interactive sites; and (iii) reduction of Au + ions to AuNPs by reductive amino acids (Figure c), as evidenced by the advent of intense purple color within 6 h and AuNP characteristic absorbance at 535 nm (Figure a). This is attributed to the slow seeding of Au atoms bound within the protein biomatrix that might have acted as nucleation centers for the slow growth of AuNPs (Video S1).…”
Section: Resultsmentioning
confidence: 99%
“…This surface protein matrix is richly structured with hydroxyl amino acids including serine, threonine, tyrosine, and hydroxyproline baring high reductive potential . Herein, area-controllable three-dimensional (3D) wide-area gold-supported catalysts between ∼80 ± 7 and 0.5 ± 0.1 cm 2 are biofabricated by utilizing the adsorptive feature, , merging with metal binding, and reductive potential , of the amino acids structured within the surface protein matrix of the discarded whole eggshells. The autogenically produced gold nanoparticles (AuNPs) of ∼9 ± 4 nm are rigidly anchored on the surface porous layer up to a depth of 2 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 lists the synthetic food dyes permitted by countries studied in this research. 3 The preceding information provides the necessary background for incorporating food dye experiments into the undergraduate laboratory curriculum. This information will enable students to make connections between chemical concepts and their application in the determination of synthetic dyes found in food colorings from around the world.…”
Section: A Brief History Of Artificial Food Colorantsmentioning
confidence: 99%
“…The use of synthetic food colorants is widespread both in the United States and around the world. While these food dyes have no nutritional value, they do brighten our soft drinks, snacks and desserts, and we all know that the appearance of food is very important . Most chemistry teachers use real-world examples to help connect chemical concepts to students’ everyday lives as evidenced by numerous articles in virtually all recent issues of this Journal .…”
mentioning
confidence: 99%